(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The role of Artificial Intelligence (AI) in database management is increasingly pivotal as organizations seek to leverage vast amounts of data for competitive advantage. AI technologies enhance traditional database systems by automating complex processes, improving data quality, and optimizing performance. This integration revolutionizes database management across several dimensions. AI facilitates automated data management by performing routine tasks such as backups, updates, and monitoring with minimal human intervention, thereby reducing errors and operational costs. Predictive analytics, driven by AI, enables organizations to anticipate future trends and behaviors based on historical data, leading to more informed strategic decisions. AI also plays a crucial role in enhancing data quality by identifying and rectifying inconsistencies, duplicates, and errors, ensuring that decision-making is based on accurate and reliable information